Labour migration in Indonesia and the health of children left behind - James Ng (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Economic research on labour migration in the developing world has traditionally focused on the role played by the remittances of overseas migrant labour in the sending country's economy. Recently, due in no small part to the availability of rich microdata, more attention has been paid to the effects of migration on the lives of family members left behind. This paper examines how the temporary migration of parents for the sole purpose of work affects the health outcomes of children left behind using longitudinal data from the Indonesian Family Life Survey (IFLS). The anthropomorphic measure of child health used, height-for-age, serves as a proxy for stunting. The evidence suggests that whether parental migration is beneficial or deleterious to child health depends on which parent moved. In particular, migration of the mother has an adverse effect on child height-for-age, reducing height-for-age Z-score by 0.5 standard deviations. This effect is not seen for father's migration.
Keywords: I15; J01; O10; 330; health; labour; migration; children; families left behind